Fault‐controlled dolomite bodies as palaeotectonic indicators and geofluid reservoirs: New insights from Gargano Promontory outcrops. Issue 7 (24th July 2017) - Rustichelli, Andrea; Iannace, Alessandro; Tondi, Emanuele; Di Celma, Claudio; Cilona, Antonino; Giorgioni, Maurizio; Parente, Mariano; Girundo, Monica; Invernizzi, Chiara
Abstract: The Upper Jurassic to Lower Cretaceous platform‐slope to basinal carbonate strata cropping out in Gargano Promontory (southern Italy) are partly dolomitized. Fieldwork and laboratory analyses (petrographic, petrophysical and geochemical) allowed the characterization of the dolomite bodies with respect to their distribution within the carbonate succession, their dimensions, geometries, textural variability, chemical stability, age, porosity, genetic mechanisms and relation with tectonics. The dolomite bodies range from metres to kilometres in size, are fault‐related and fracture‐related, and probably formed during the Early Cretaceous at <500 m burial depths and temperatures <50°C. The proposed dolomitization model relies on mobilization of Early Cretaceous seawater that flowed, downward and then upward, along faults and fractures and was modified in its isotopic composition moving through Triassic and Jurassic strata that underlie the studied dolomitized succession. Despite the numerous cases reported in literature, this study demonstrates that hydrothermal and/or high‐temperature fluids are not necessarily required for fault‐controlled dolomitization. Distribution and geometries of dolomite bodies can be used for palaeotectonic reconstructions, as they partly record the characteristics (size, attitude and kinematics) of the palaeo‐faults, even if not preserved, that controlled dolomitization. In Gargano Promontory, dolomites record Early Cretaceous palaeo‐faults from metres to kilometres long, striking north‐west/south‐east to east/west and characterized by normal to strike‐slip kinematics. Dolomitization increases the matrix porosity by up to 7% and, therefore, can improve the geofluid storage capacity of tight, platform‐slope to basinal limestones. The results have a great significance for characterization of geofluid (for example, hydrocarbons) reservoirs hosted in similar dolomitized carbonate successions. Distribution, size and shapes of reservoir rocks (i.e. dolomite bodies) could be broadly predictable if the characteristics of the palaeo‐fault system present at the time of dolomitization are known.